PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PELAJARAN SKI KELAS V SDI DARUSSALAM SUMBERREJO BOJONEGORO - Nila Dwi Susanti (JUSEDA, 2020)
From the learning outcomes of SDI Darussalam Dungmas students through Classroom Action Research (CAR) that using audio visual media has covered all learning material in SKI lessons properly and correctly. Through this audio visual media will be able to help students in the teaching and learning process, will make students better understand, and more happy in following the SKI learning process, so students will not quickly get bored and busy, and students will be very interested in finding the SKI Learning process , so that the learning atmosphere in the class will also be more fun, so that student learning outcomes can also be better and more improved. Based on the results of researcher observation in class V at SDI Darussalam Dungmas Kedungrejo, there are still some students who get and get low learning outcomes in SKI lessons in class V. The low student learning outcomes can be seen from the results of tests given by the teacher. Most of them are still the majority of students who still do not meet the minimum completeness criteria value (KKM). Of the KKM that have been determined by the school that is 80 there are still many students who get grades below the KKM requirements. The average value of students obtained at the time of daily tests and the value of assignments is only 70, even the majority of students still get and get a value of 60-50. From the results of Classroom Action Research (CAR) student learning outcomes can be higher than good in SKI learning, so students are able to achieve the KKM value, the value obtained by students from learning outcomes in the pre-cycle is (63.75) and cycle I has reached ( 75) and can be increased in cycle II to (90) it can show the use of audio-visual media can improve student learning outcomes.